(3Gdbhd GdJGe aj aVd GdQei HGdSgGes - (3GdSNGhj , TeS GdOjf eMeO Hf YHO GdQMef Hf eMeO GdSNGhj, GdSNGhj,J (B902 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QGei GdYOh HGdSge GdYQHi GdCTQa adeG cGf GdQei HGdSgGe ef GLd GfhGY GdaQhSjg s
(3BNQgG (B:s
(3CHj GdeHGQc LSJg GdaVjd QMegeG Gddg JYGdi hbGd jG eYde GdNjQ ef jMSf gPG ZjQc BNQ Gdbhd GdJGe hGdMeO ddg hMeOg hGdUdGg Ydi HOQ GdJeGe eMeO Ydjg GaVd GdUdGg hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B194 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B150s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdeLGejYs